Effect of substrate competition in kinetic models of metabolic networks. Issue 17 (26th June 2013) - Schäuble, Sascha; Stavrum, Anne Kristin; Puntervoll, Pål; Schuster, Stefan; Heiland, Ines
Abstract : Substrate competition can be found in many types of biological processes, ranging from gene expression to signal transduction and metabolic pathways. Although several experimental and in silico studies have shown the impact of substrate competition on these processes, it is still often neglected, especially in modelling approaches. Using toy models that exemplify different metabolic pathway scenarios, we show that substrate competition can influence the dynamics and the steady state concentrations of a metabolic pathway. We have additionally derived rate laws for substrate competition in reversible reactions and summarise existing rate laws for substrate competition in irreversible reactions.